Antitumor Efficacy of Interleukin 12-Transfected Mesenchymal Stem Cells in B16-F10 Mouse Melanoma Tumor Model - Urška Kamenšek; Tim Božič; Maja Čemažar; Urban Švajger (Pharmaceutics)
Background/Objectives: Mesenchymal stromal cells (MSCs) hold the potential for tumor-targeted gene delivery due to their ex vivo manipulability, low immunogenicity, scalability, and inherent tumor-homing properties. Despite the widespread use of viral vectors for MSC genetic modification, safety concerns have prompted interest in non-viral alternatives, such as gene electrotransfer (GET). This study aimed to optimize GET parameters for MSCs transfection, assess MSCs biodistribution after in vivo administration, and evaluate the therapeutic potential of interleukin-12 (IL-12)-modified MSCs in a mouse melanoma model. Methods: Human MSCs were isolated from umbilical cords under ethically approved protocols. GET protocols were optimized using a fluorescent reporter gene to evaluate transfection efficiency and cell viability. MSC biodistribution was examined following intravenous and intratumoral injections in murine tumor models using luminescent reporter gene. The therapeutic efficacy of IL-12-modified MSCs was assessed in a syngeneic mouse melanoma model. Results: Optimized GET protocols achieved a transfection efficiency of 80% and a cell viability of 90%. Biodistribution studies demonstrated effective tumor retention of MSCs following intratumoral injections, whereas intravenous administration resulted in predominant cell localization in the lungs. IL-12-modified MSCs injected intratumorally significantly inhibited tumor growth, delaying tumor progression by five days compared to controls. Conclusions: Optimized GET conditions enabled high-efficiency, high-viability MSCs transfection, facilitating their use as effective vehicles for localized cytokine delivery. While the innate tumor tropism of MSCs was not conclusively demonstrated, the study highlights the potential of GET as a reliable non-viral gene delivery platform and underscores the therapeutic promise of IL-12-modified MSCs in tumor-targeted gene therapy.